2023
DOI: 10.1377/hlthaff.2022.00523
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Uncovered Costs For HIV Preexposure Prophylaxis In The US, 2018

Abstract: The cost of HIV preexposure prophylaxis (PrEP) medication and care is a key barrier to PrEP use. Using population-based surveys and published information, we estimated the number of people with uncovered costs for PrEP care among US adults with PrEP indications, stratified by HIV transmission risk group, insurance status, and income. Accounting for existing PrEP payer mechanisms, we estimated annual uncovered costs for PrEP medication, clinical visits, and laboratory testing based on the 2021 PrEP clinical pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
2
0
0
Order By: Relevance
“…McManus et al found that coverage for PrEP medications was high among qualified health plans, which is consistent with reports suggesting that most people can access PrEP at low or no cost . However, the study’s results are also consistent with prior evidence that it is often not the out-of-pocket costs but the complexity of obtaining financial coverage—through health plans for insured people or assistance programs for uninsured people—that deters people from using PrEP .…”
supporting
confidence: 86%
See 1 more Smart Citation
“…McManus et al found that coverage for PrEP medications was high among qualified health plans, which is consistent with reports suggesting that most people can access PrEP at low or no cost . However, the study’s results are also consistent with prior evidence that it is often not the out-of-pocket costs but the complexity of obtaining financial coverage—through health plans for insured people or assistance programs for uninsured people—that deters people from using PrEP .…”
supporting
confidence: 86%
“…The 2 medications were priced at over $20 000 annually per person during the study period, 3 making coverage essential for those accessing PrEP through insurance plans.McManus et al 3 found that coverage for PrEP medications was high among qualified health plans, which is consistent with reports suggesting that most people can access PrEP at low or no cost. 4 However, the study's results are also consistent with prior evidence that it is often not the out-of-pocket costs but the complexity of obtaining financial coverage-through health plans for insured people or assistance programs for uninsured people-that deters people from using PrEP. 5 The authors 3 found that 15% to 20% of plans placed PrEP medications on specialty tiers and that prior authorization requirements were common, particularly for emtricitabine/tenofovir disoproxil fumarate, the older medication.…”
supporting
confidence: 82%
“…MSM and transgender women) participants located in Miami were less likely to utilize PrEP beyond completion of a demonstration project study compared to those in San Francisco [61]. This highlights the critical role that insurance access plays in limiting the potential scale of PrEP interventions [20,62,63]. As health insurance coverage continues to be a substantial barrier in limiting the potential scale of PrEP, Medicaid expansion and PrEP Drug Assistance Programs improve equity in access to care in addition to policies that increase PrEP coverage and reduce related costs in insurance plans, and interventions which offer PrEP at no cost regardless of insurance coverage or immigration status [22,23,64,65].…”
Section: Discussionmentioning
confidence: 99%